'Charter flights full of homosexuals'. The Changing Rights of Homosexual Immigrants in The Netherlands, 1945-1992. - Marlou Schrover; Frerik Kampman (Tijdschrift voor Sociale en Economische Geschiedenis, 2020)
This article seeks to explain changes in Dutch policies regarding the rights of homosexual immigrants. In the period 1945-1992 policies changed fundamentally. As this article will show, existing theories do not fully explain why policies regarding homosexual foreigners changed. The most striking aspect of the policy changes was the casualness with which decision were taken, and the long time that passed before the consequences of decisions sank in. Although the number of homosexual foreigners coming to the Netherlands was never large, their migration was always highly contested: response to their claims was a key part of how the nation defined itself, both now and in the past. This article shows how discussions about the right to refugee status for homosexual foreigners evolved from debates about the right of homosexual migrants to come within the framework of labour migration or family migration (right to live with your partner). Policies changed – this article argues - because this issue was not at the heart of policy fields (labour migration, family migration, refugee migration) but rather at the points where policy fields intersected, which made foreseeing consequences more difficult.